Solid electrolyte material and battery using the same
By using solid electrolyte materials including Li, Y, X, O and H, the problem of insufficient lithium ion conductivity in the prior art is solved, and high lithium ion conductivity and excellent battery charge and discharge characteristics and safety are achieved.
Patent Information
- Application Number
- CN202080037195.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-09
- Filing Date
- 2020-03-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-03-04
AI Technical Summary
The prior art is difficult to provide solid electrolyte materials with high lithium ion conductivity, which affects the charge and discharge characteristics and safety of the battery.
A solid electrolyte material containing Li, Y, X, O and H, wherein X is a material selected from at least two elements of F, Cl, Br and I, and the ionic conductivity of the material is improved by adjusting the molar ratio and process conditions of the raw material powder.
High lithium ion conductivity is achieved, the charging and discharging characteristics and safety of the battery are improved, and the production of hydrogen sulfide is avoided.
Smart Images

Figure CN113853696B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte material and a battery using the solid electrolyte material. Background Art
[0002] Patent Document 1 discloses a solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses a solid-state battery using Li 6-3z Y z A solid electrolyte material represented by X6 (satisfying 0<z<2 and X is Cl or Br).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-129312
[0006] Patent Document 2: International Publication No. 2018 / 025582 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present invention is to provide a solid electrolyte material having high lithium ion conductivity.
[0009] Means for solving problems
[0010] The solid electrolyte material of the present invention contains Li, Y, X, O, and H, wherein X is at least two elements selected from the group consisting of F, Cl, Br, and I.
[0011] Effects of the Invention
[0012] According to the present invention, a solid electrolyte material having high lithium ion conductivity is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.
[0014] Figure 2 It is a figure which shows the X-ray diffraction spectrum of the solid electrolyte material of Examples 1-3.
[0015] Figure 3 A schematic diagram showing a press mold 300 used to evaluate the ion conductivity of a solid electrolyte material.
[0016] Figure 4 It is a graph of a Cole-Cole plot showing the impedance measurement results of the solid electrolyte material of Example 1.
[0017] Figure 5It is a graph showing the initial discharge characteristics of the batteries of Example 1 and Comparative Example 1.
[0018] Figure 6 It is a graph showing the infrared absorption spectra of the solid electrolyte materials of Examples 1 to 3. DETAILED DESCRIPTION
[0019] Hereinafter, embodiments of the present invention will be described with reference to the drawings.
[0020] (First Embodiment)
[0021] The solid electrolyte material of the first embodiment contains Li, Y, X, O, and H. X is at least two elements selected from the group consisting of F, Cl, Br, and I. The solid electrolyte material of the first embodiment has high lithium ion conductivity.
[0022] The solid electrolyte material of the first embodiment can be used to obtain an all-solid battery having excellent charge and discharge characteristics. The all-solid battery may be a primary battery or a secondary battery.
[0023] The solid electrolyte material of the first embodiment preferably does not contain sulfur. The solid electrolyte material that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere. Therefore, when the solid electrolyte material of the first embodiment does not contain sulfur, the battery using the solid electrolyte material has excellent safety. It should be noted that the sulfide solid electrolyte disclosed in Patent Document 1 generates hydrogen sulfide when exposed to the atmosphere.
[0024] In order to improve the ionic conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further contain at least one element selected from Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.
[0025] The solid electrolyte material of the first embodiment may be formed of Li, Y, X, O, and H in order to improve the ion conductivity of the solid electrolyte material.
[0026] In order to improve the ion conductivity of the solid electrolyte material, in the solid electrolyte material of the first embodiment, O and H are bonded together, and O bonded to H may also exist in the surface region of the solid electrolyte material.
[0027] In order to improve the ion conductivity of the solid electrolyte material, X may be Cl and Br. In this case, the molar fraction of Cl in X may be higher than the molar fraction of Br. Thus, the solid electrolyte material of the first embodiment becomes lighter.
[0028] The X-ray diffraction pattern of the solid electrolyte material of the first embodiment can be measured using Cu-Kα. In the obtained X-ray diffraction pattern, peaks may also exist in the range of diffraction angles 2θ of 13.6° to 14.6°, 27.8° to 29.0°, 32.0° to 33.3°, 46.3° to 47.8°, and 57.2° to 59.8°. This solid electrolyte material has high ion conductivity.
[0029] When the molar ratio of Li to Y is set to x, the molar ratio of Cl to Y is set to y, and the molar ratio of Br to Y is set to z, the following three mathematical formulas can also be satisfied:
[0030] 2.7≤x≤3.4,
[0031] 3.4≤y≤4.3, and
[0032] 1.9≤z≤2.5. This solid electrolyte material has high ion conductivity.
[0033] The following three formulas can also be satisfied:
[0034] 3.02≤x≤3.05,
[0035] 3.63≤y≤3.81, and
[0036] 2.13≤z≤2.19. This solid electrolyte material has higher ion conductivity.
[0037] When the molar ratio of O to Y is set to a, 0<a≤0.42 may also be satisfied. This solid electrolyte material has high ion conductivity.
[0038] 0<a≤0.19 may also be satisfied. Such a solid electrolyte material has higher ion conductivity.
[0039] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a manner having a pellet or a plate shape.
[0040] For example, when the shape of the solid electrolyte material of the first embodiment is a particle shape (for example, a spherical shape), the solid electrolyte material of the first embodiment may have a median particle size of 0.1 μm or more and 100 μm or less.
[0041] In order to improve the ion conductivity of the solid electrolyte material of the first embodiment and to disperse the solid electrolyte material and active material of the first embodiment well, the median particle size may be 0.5 μm or more and 10 μm or less. In order to further disperse the solid electrolyte material and active material of the first embodiment well, the solid electrolyte material of the first embodiment may have a median particle size smaller than that of the active material.
[0042] <Method for producing solid electrolyte material>
[0043] The solid electrolyte material of the first embodiment can be produced by the following method.
[0044] First, the raw material powders of the halides are mixed.
[0045] As an example, when synthesizing a solid electrolyte material formed by Li, Y, Cl, Br, O and H, YCl3 raw material powder, LiCl raw material powder and LiBr raw material powder are mixed. The obtained mixed powder is calcined in an inert gas atmosphere (for example, an argon atmosphere with a dew point below -60°C) in which the oxygen concentration and water concentration are adjusted. The obtained reactant is allowed to stand in an atmosphere with a higher dew point (for example, an argon atmosphere with a dew point of -30°C). The raw material powders can also be mixed at a pre-adjusted molar ratio in a manner that offsets the composition changes that may occur in the synthesis process. The amount of oxygen in the solid electrolyte material is determined by selecting the raw material powder, the oxygen concentration in the atmosphere, the water concentration in the atmosphere and the reaction time. In this way, the solid electrolyte material of the first embodiment is obtained.
[0046] By selecting the raw material powders and the mixing ratio of the raw material powders, various halides can be obtained.
[0047] An example of the halide is Li 3.1 Y 0.9 Ca 0.1 Br3Cl3、Li 3.1 Y 0.9 Mg 0.1 Cl3、Li 2.4 Y 0.8 Ca 0.6 Br2I2F2, Li3YBr5F, Li 2.7 Y 1.1 Br3Cl3、Li 2.7 Y 1.1 BrCl5、Li 3.3 Y 0.9 Br3Cl3, Li3YBrCl5, Li3YBr4Cl2, or Li3YBr 0.5 Cl 5.5 .
[0048] These halides have high ion conductivity. By exposing these halides to an atmosphere with a high dew point, a solid electrolyte material incorporating oxygen and hydrogen is obtained. The solid electrolyte material thus obtained can also have high ion conductivity.
[0049] (Second Embodiment)
[0050] The second embodiment will be described below, and matters described in the first embodiment will be omitted as appropriate.
[0051] The battery of the second embodiment comprises a positive electrode, an electrolyte layer and a negative electrode. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment. The battery of the second embodiment has excellent charge and discharge characteristics because it contains the solid electrolyte material of the first embodiment.
[0052] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.
[0053] The battery 1000 includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203. The electrolyte layer 202 includes an electrolyte material (for example, a solid electrolyte material). The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100.
[0054] The solid electrolyte particle 100 is a particle containing the solid electrolyte material of the first embodiment as a main component. The solid electrolyte particle 100 may be a particle formed of the solid electrolyte material of the first embodiment.
[0055] The positive electrode 201 contains a material capable of inserting and extracting metal ions (for example, lithium ions), such as a positive electrode active material (for example, positive electrode active material particles 204 ).
[0056] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are LiNi 1-d-f Co d Al f O2 (where 0<d, 0<f and 0<(d+f)<1) or LiCoO2.
[0057] In the positive electrode 201, in order to make the positive electrode active material particles 204 and the solid electrolyte particles 100 well dispersed, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery 1000 are improved. In order to make lithium diffuse rapidly in the positive electrode active material particles 204, the positive electrode active material particles 204 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery 1000 can operate at a high output power. As described above, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more and 100 μm or less.
[0058] In the positive electrode 201 , in order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well, the positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100 .
[0059] To improve the energy density and output of the battery 1000 , in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0060] In order to increase the energy density and output of the battery 1000 , the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0061] The electrolyte layer 202 contains an electrolyte material. The electrolyte material may be the solid electrolyte material of the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.
[0062] The electrolyte layer 202 may be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.
[0063] Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI. Here, X' is at least one element selected from F, Cl, Br and I.
[0064] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0065] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may also be uniformly dispersed. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.
[0066] In order to suppress short circuit between the positive electrode 201 and the negative electrode 203 and improve the output of the battery, the electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less.
[0067] The negative electrode 203 contains a material capable of inserting and removing metal ions (for example, lithium ions), such as a negative electrode active material (for example, negative electrode active material particles 205 ).
[0068] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds, or tin compounds.
[0069] In the negative electrode 203, in order to make the negative electrode active material particles 205 and the solid electrolyte particles 100 well dispersed, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery are improved. In order to quickly diffuse lithium in the negative electrode active material particles 205, the negative electrode active material particles 205 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery can operate at a high output power. As described above, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more and 100 μm or less.
[0070] In the negative electrode 203 , in order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well, the negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100 .
[0071] In order to improve the energy density and output of the battery 1000 , in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0072] In order to increase the energy density and output of the battery 1000 , the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0073] In order to improve ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material.
[0074] As described above, the second solid electrolyte material may also be a halide solid electrolyte. Examples of halide solid electrolytes are Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI. Here, X' is an element selected from at least one of F, Cl, Br and I.
[0075] The second solid electrolyte material may also be a sulfide solid electrolyte.
[0076] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 .
[0077] The second solid electrolyte material may also be an oxide solid electrolyte.
[0078] Examples of oxide solid electrolytes are
[0079] (i) NASICON type solid electrolytes such as LiTi2(PO4)3 or its element substitution products,
[0080] (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3,
[0081] (iii)Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution bodies,
[0082] (iv)Li7La3Zr2O 12 Or a garnet-type solid electrolyte such as an element-substituted body thereof, or (v) Li3PO4 or its N-substituted body.
[0083] The second solid electrolyte material may also be an organic polymer solid electrolyte.
[0084] Examples of organic polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure may contain a large amount of lithium salt, thereby further improving ion conductivity.
[0085] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0086] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid for the purpose of facilitating the transfer of lithium ions and improving the output characteristics of the battery 1000 .
[0087] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0088] Examples of the non-aqueous solvent include cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of the cyclic carbonate solvent include ethylene carbonate, propylene carbonate, or butylene carbonate.
[0089] Examples of the chain carbonate solvent are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate.
[0090] Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane.
[0091] Examples of the chain ether solvent are 1,2-dimethoxyethane or 1,2-diethoxyethane.
[0092] An example of a cyclic ester solvent is gamma-butyrolactone.
[0093] An example of the chain ester solvent is methyl acetate.
[0094] Examples of the fluorine solvent are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate.
[0095] One nonaqueous solvent selected therefrom may be used alone, or a mixture of two or more nonaqueous solvents selected therefrom may be used.
[0096] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0097] The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter or more and 2 mol / liter or less.
[0098] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0099] Examples of cations contained in ionic liquids are
[0100] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,
[0101] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium, or piperidinium; or
[0102] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0103] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - The ionic liquid may also contain lithium salts.
[0104] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder in order to improve adhesion between particles.
[0105] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber or carboxymethyl cellulose.
[0106] Copolymers can also be used as binders. Examples of such binders are copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from the above materials can also be used as a binder.
[0107] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent in order to improve electronic conductivity.
[0108] Examples of conductive additives are
[0109] (i) Graphites such as natural graphite or artificial graphite,
[0110] (ii) Carbon black such as acetylene black or Ketjen black,
[0111] (iii) conductive fibers such as carbon fibers or metal fibers,
[0112] (iv) fluorinated carbon,
[0113] (v) Metal powders such as aluminum,
[0114] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0115] (vii) conductive metal oxides such as titanium oxide, or
[0116] (viii) Conductive polymer compounds such as polyaniline, polypyrrole, or polythiophene. For cost reduction, the conductive auxiliary agent described in (i) or (ii) above may also be used.
[0117] Examples of the shape of the battery of the second embodiment are a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.
[0118] (Example)
[0119] The present invention will be described in detail with reference to the following examples.
[0120] 《Example 1》
[0121] [Production of solid electrolyte materials]
[0122] In an argon atmosphere with a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), YCl3, LiCl and LiBr are prepared as raw material powders in a manner to achieve a YCl3:LiCl:LiBr molar ratio of about 1:1:2. These powders are crushed and mixed in a mortar. Then, the mixture is calcined in an aluminum crucible at 500°C for 1 hour and then crushed in a mortar. The resulting reactant is allowed to stand for about 3 minutes in an atmosphere with a dew point of -30°C. In this way, the solid electrolyte material of Example 1 is obtained.
[0123] [Composition analysis of solid electrolyte materials]
[0124] The composition analysis of the solid electrolyte material of Example 1 was carried out in a dry argon atmosphere.
[0125] The contents of Li and Y per unit weight of the solid electrolyte material of Example 1 were measured using high-frequency inductively coupled plasma emission spectrometry. The contents of Cl and Br in the solid electrolyte material of Example 1 were measured using an ion chromatograph (manufactured by Dionex, ICS-2000) using ion chromatography. Based on the contents of Li:Y:Cl:Br obtained from these measurement results, the molar ratio of Li:Y:Cl:Br was calculated. As a result, the solid electrolyte material of Example 1 had a molar ratio of Li:Y:Cl:Br of 3.02:1.00:3.81:2.19.
[0126] The mass of O in Example 1 was measured by non-dispersive infrared absorption method using an oxygen-nitrogen-hydrogen analyzer (manufactured by Horiba, Ltd., EMGA-930) relative to the mass of the entire solid electrolyte material. The result was 0.59%. Based on this, the molar ratio of Y:O was calculated. As a result, the solid electrolyte material of Example 1 had a molar ratio of Y:O of 1.00:0.16.
[0127] In the composition analysis, elements having a molar fraction of 0.001% or less relative to Y are regarded as impurities.
[0128] The solid electrolyte material of Example 1 was analyzed by total reflection measurement using an infrared spectrometer (manufactured by BRUKER, ALPHA). The prism was made of diamond. As a result, in the case of protons (H + ) with oxygen bond at 3100cm -1 ~3640cm -1The surface region of the present invention refers to the region measured in this way. That is, the surface region of the solid electrolyte material of the first embodiment is about 1 μm from the surface of the solid electrolyte material toward the inside. The infrared absorption spectrum of the solid electrolyte material of Example 1 is shown in Figure 6 middle.
[0129] [X-ray diffraction]
[0130] The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured using an X-ray diffraction device (Rigaku Co., Ltd., MiniFlex600) in a dry environment with a dew point of -45°C or less. Cu-Kα rays (wavelength and ).
[0131] The results of X-ray diffraction measurement showed that peaks existed at 14.13°, 28.24°, 28.57°, 32.84°, 47.35° and 59.20°. The X-ray diffraction pattern of the solid electrolyte material of Example 1 is shown in Figure 2 middle.
[0132] [Evaluation of ion conductivity]
[0133] Figure 3 A schematic diagram of a press mold 300 used for evaluating the ion conductivity of a solid electrolyte material is shown. The press mold 300 includes a frame mold 301, a punch lower portion 302, and a punch upper portion 303. The frame mold 301 is formed of insulating polycarbonate. The punch upper portion 303 and the punch lower portion 302 are both formed of electron conductive stainless steel.
[0134] use Figure 3 The press molding die 300 shown was used to measure the ion conductivity of the solid electrolyte material of Example 1 by the following method.
[0135] In a dry argon atmosphere, the powder of the solid electrolyte material of Example 1 was filled into the press mold 300. Inside the press mold 300, a pressure of 400 MPa was applied to the solid electrolyte material of Example 1 using the punch lower portion 302 and the punch upper portion 303.
[0136] The impedance of the solid electrolyte material of Example 1 was measured at room temperature by electrochemical impedance spectroscopy using a potentiostat (Versa STAT4, Princeton Applied Research) via the punch upper portion 303 and the punch lower portion 302 while maintaining the pressure applied. The punch upper portion 303 was connected to the working electrode and the potential measurement terminal. The punch lower portion 302 was connected to the counter electrode and the reference electrode.
[0137] Figure 4 It is a graph of a Cole-Cole plot showing the impedance measurement results.
[0138] Figure 4 In the example, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material of Example 1 to ion conduction. Figure 4 The arrow R SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (2).
[0139] σ=(R SE ×S / t) -1 (2)
[0140] Here, σ is the ion conductivity. S is the contact area between the solid electrolyte material and the upper portion 303 of the punch ( Figure 3 is equivalent to the cross-sectional area of the hollow portion of the frame mold 301). SE is the resistance value of the solid electrolyte material in the impedance measurement. t is the thickness of the solid electrolyte material to which pressure is applied ( Figure 3 , the thickness of the layer formed by the powder 101 of the solid electrolyte material).
[0141] The ionic conductivity of the solid electrolyte material of Example 1 measured at 25°C was 1.3×10 -3 S / cm.
[0142] [Battery production]
[0143] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO2 as an active material were prepared so as to have a volume ratio of 70:30. These materials were mixed in an agate mortar to obtain a mixture.
[0144] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (156 mg), the above-mentioned mixture (10.0 mg) and aluminum powder (14.7 mg) were stacked in order. A pressure of 300 MPa was applied to the stack to form a first electrode and a solid electrolyte layer. The solid electrolyte layer had a thickness of 700 μm.
[0145] Next, a metal In foil was stacked on the solid electrolyte layer. The solid electrolyte layer was sandwiched between the metal In foil and the first electrode. The metal In foil had a thickness of 200 μm. Next, a pressure of 80 MPa was applied to the metal In foil, thereby forming a second electrode.
[0146] A current collector made of stainless steel was mounted on the first electrode and the second electrode, and then a current collecting lead was mounted on the current collector. Finally, an insulating hoop was used to block the inside of the insulating tube from the outside air atmosphere, and the inside of the tube was sealed. In this way, the battery of Example 1 was obtained.
[0147] [Charge and discharge test]
[0148] The obtained battery of Example 1 was placed in a constant temperature chamber at 25°C.
[0149] The battery of Example 1 was charged at a current value that gave a 0.05C rate (20 hour rate) relative to the theoretical capacity of the battery until the voltage reached 3.7V.
[0150] Next, the battery of Example 1 was discharged at a current value corresponding to a 0.05C rate until the voltage reached 1.9V.
[0151] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 70 μAh.
[0152] 《Examples 2 and 3》
[0153] [Production of solid electrolyte materials]
[0154] The solid electrolyte material of Example 2 was obtained in the same manner as in Example 1 except that the reaction product was allowed to stand in an atmosphere having a dew point of -30°C for 1 hour instead of about 3 minutes.
[0155] A solid electrolyte material of Example 3 was obtained in the same manner as in Example 1 except that the reactant was allowed to stand in an atmosphere having a dew point of -30°C for 2 hours instead of about 3 minutes.
[0156] [Composition analysis of solid electrolyte materials]
[0157] The composition analysis of the solid electrolyte materials of Examples 2 and 3 was carried out in the same manner as in Example 1. The mass of O in Examples 2 and 3 was 0.69% and 1.59%, respectively, based on the mass of the entire solid electrolyte material.
[0158] The results of measurement using an infrared spectrometer showed that the solid electrolyte materials of Examples 2 and 3 had a bond between a proton and oxygen. The infrared spectra of the solid electrolyte materials of Examples 2 and 3 are shown in FIG. Figure 6 middle.
[0159] [X-ray diffraction]
[0160] In the same manner as in Example 1, X-ray diffraction patterns of the solid electrolyte materials of Examples 2 and 3 were measured.
[0161] In the X-ray diffraction spectrum of the solid electrolyte material of Example 2, peaks exist at 14.15°, 28.26°, 28.59°, 32.85°, 47.38°, and 59.22°.
[0162] In the X-ray diffraction spectrum of the solid electrolyte material of Example 3, peaks exist at 14.13°, 28.24°, 28.58°, 32.83°, 47.35°, and 59.20°.
[0163] Therefore, the solid electrolyte materials of Examples 2 and 3 have peaks at diffraction angles substantially the same as those of Example 1. The X-ray diffraction patterns are shown in Figure 2 middle.
[0164] [Evaluation of ion conductivity]
[0165] The ion conductivities of the solid electrolyte materials of Examples 2 and 3 were measured in the same manner as in Example 1. Table 1 shows the measured ion conductivities.
[0166] [Battery production]
[0167] Using the solid electrolyte materials of Examples 2 and 3, batteries of Examples 2 and 3 were obtained in the same manner as in Example 1.
[0168] [Charge and discharge test]
[0169] Using the batteries of Examples 2 and 3, a charge and discharge test was carried out in the same manner as in Example 1.
[0170] The batteries of Examples 2 and 3 can be charged and discharged as well as the battery of Example 1.
[0171] Comparative Example 1
[0172] In a dry argon atmosphere, LiCl and FeCl2 were prepared as raw material powders in a LiCl:FeCl2 molar ratio of 2:1. These powders were ground using a planetary ball mill for 25 hours at 600 rpm in a mechanochemical reaction. Thus, a solid electrolyte material of Comparative Example 1 was obtained. The solid electrolyte material of Comparative Example 1 has a composition represented by Li2FeCl4.
[0173] The ion conductivity of the solid electrolyte material of Comparative Example 1 was measured in the same manner as in Example 1. As a result, the ion conductivity measured at 22° C. was 9×10 -6 S / cm.
[0174] A battery of Comparative Example 1 was obtained in the same manner as in Example 1. A charge and discharge test was performed using this battery. The battery of Comparative Example 1 had an initial discharge capacity of 1 uAh or less. That is, the battery of Comparative Example 1 was neither charged nor discharged.
[0175] Table 1
[0176]
[0177] Investigation
[0178] Table 1 shows that the solid electrolyte materials of Examples 1 to 3 have a 1×10 -4 High ion conductivity of more than S / cm.
[0179] For a, which represents the molar ratio of O to Y, when 0<a≤0.42 is satisfied, the solid electrolyte material has high ion conductivity. Comparison of Examples 1 and 2 with Example 3 shows that when 0<a≤0.19 is satisfied, the solid electrolyte material has a higher 1×10 -3 Ionic conductivity of S / cm.
[0180] Depend on Figure 2 It is shown that the solid electrolyte materials of Examples 1 to 3 have peaks at the same diffraction angle in the X-ray diffraction patterns.
[0181] Depend on Figure 6 It is confirmed that the solid electrolyte materials of Examples 1 to 3 have oxygen bonded to protons. It is believed that the oxygen exists as hydroxyl groups or hydrated water. In the manufacturing process of the solid electrolyte material, when the solid electrolyte material is exposed to an atmosphere with a high dew point, the moisture in the atmosphere is incorporated into the solid electrolyte material. It can be predicted that the halogen elements near the surface of the solid electrolyte material are replaced by hydroxyl groups.
[0182] In the composition analysis of solid electrolyte materials, measurement errors will also occur when the same sample is measured repeatedly. The maximum measurement error can be about 20%.
[0183] The batteries of Examples 1 to 3 could be charged and discharged at room temperature. On the other hand, the battery of Comparative Example 1 could not be charged and discharged.
[0184] Since the solid electrolyte materials of Examples 1 to 3 do not contain sulfur, they do not generate hydrogen sulfide.
[0185] As described above, the solid electrolyte material of the present invention is suitable for providing a battery having high lithium ion conductivity and capable of good charge and discharge.
[0186] Industrial Applicability
[0187] The battery of the present invention is used, for example, in an all-solid lithium ion secondary battery.
[0188] Explanation of symbols:
[0189] 100 Solid electrolyte particles 101 Powder of solid electrolyte material
[0190] 201 positive electrode 202 electrolyte layer
[0191] 203 Negative electrode 204 Positive electrode active material particles
[0192] 205 Negative electrode active material particles 300 Pressurized molding die
[0193] 301 frame mold 302 punch lower part
[0194] 303 Punch Upper 1000 Battery
Claims
1. A solid electrolyte material comprising Li, Y, X, O and H, wherein: X is at least two elements selected from F, Cl, Br and I, In the X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays, peaks exist in the ranges of diffraction angles 2θ of 13.6° to 14.6°, 27.8° to 29.0°, 32.0° to 33.3°, 46.3° to 47.8°, and 57.2° to 59.8°.
2. The solid electrolyte material according to claim 1, further comprising at least one element selected from the group consisting of Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb. The solid electrolyte material according to claim 1 , which is composed of Li, Y, X, O and H. . 4 . The solid electrolyte material according to claim 1 , wherein O and H are bonded together, and O exists in a surface region of the solid electrolyte material.
5. The solid electrolyte material according to any one of claims 1 to 3, wherein X is Cl and Br.
6. The solid electrolyte material according to claim 5, wherein In X, the mole fraction of Cl is higher than the mole fraction of Br.
7. The solid electrolyte material according to claim 5, which satisfies the following three mathematical formulas: 2.7≤x≤3.4、 3.4≤y≤4.3, and 1.9≤z≤2.5, Here, x represents the molar ratio of Li to Y, y represents the molar ratio of Cl to Y, and z represents the molar ratio of Br to Y.
8. The solid electrolyte material according to claim 7, which satisfies the following three mathematical formulas: 3.02≤x≤3.05、 3.63≤y≤3.81, and 2.13≤z≤2.19。 9 . The solid electrolyte material according to claim 1 , which satisfies the mathematical formula: 0<a≤0.42, where a represents a molar ratio of O to Y. 10 . The solid electrolyte material according to claim 9 , which satisfies the mathematical formula: 0<a≤0.
19.
11. A battery comprising: positive electrode, Negative electrode, and An electrolyte layer is provided between the positive electrode and the negative electrode, wherein At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 10.
Citation Information
Patent Citations
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Solid electrolyte material, and cell
WO2018025582A1
Preparation method of lithium yttrium halide and application thereof in solid electrolyte and battery
CN109775744A